2013
DOI: 10.1002/biot.201200371
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering for metabolic engineering: Current and next‐generation tools

Abstract: Protein engineering in the context of metabolic engineering is increasingly important to the field of industrial biotechnology. As the demand for biologically-produced food, fuels, chemicals, food additives, and pharmaceuticals continues to grow, the ability to design and modify proteins to accomplish new functions will be required to meet the high productivity demands for the metabolism of engineered organisms. This article reviews advances of selecting, modeling, and engineering proteins to improve or alter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 79 publications
(99 reference statements)
0
28
0
Order By: Relevance
“…Rational approaches to engineer protein have been largely pursued via manipulation of amino acid residues in the catalytic pocket achieved via site directed mutagenesis (Marcheschi et al, 2013). In order to promote non-native catalysis toward larger substrates, increasing the catalytic pocket has been the predominant strategy, generally achieved via replacement of target residues with smaller ones (Marcheschi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rational approaches to engineer protein have been largely pursued via manipulation of amino acid residues in the catalytic pocket achieved via site directed mutagenesis (Marcheschi et al, 2013). In order to promote non-native catalysis toward larger substrates, increasing the catalytic pocket has been the predominant strategy, generally achieved via replacement of target residues with smaller ones (Marcheschi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Rational approaches to engineer protein have been largely pursued via manipulation of amino acid residues in the catalytic pocket achieved via site directed mutagenesis (Marcheschi et al, 2013). In order to promote non-native catalysis toward larger substrates, increasing the catalytic pocket has been the predominant strategy, generally achieved via replacement of target residues with smaller ones (Marcheschi et al, 2013). Additionally, substituting target residues via saturation mutagenesis (Savile et al, 2010) and/or directed evolution (Kan et al, 2016) have been shown to improve catalysis possibly due to changes in the above mentioned interactions altering catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of protein engineering continue to grow, impacting research and development in technologies that include pharmaceuticals and therapeutics (Bommarius et al, ; Fisher and Tullman‐Ercek, ; and ), biosensing (Gredell et al, ), synthetic biology (Cirino and Qian, ), and industrial production of fuels and chemicals (Fisher and Tullman‐Ercek, ; Marcheschi et al, ). Mounting understanding of the native functional roles of proteins, and of protein sequence‐structure‐function relationships, offers new insights into how proteins may be engineered for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, understanding structures-functions of proteins has not yet become a straightforward task: proteins arising out due to divergent evolutions are similar in their amino acid sequences and three-dimensional (3D) folds but drastically differing in their functions; in contrast, proteins arising out due to convergent evolutions are differing in their primary structures and biological activities but maintain similar 3D folds (Grishin, 2001;Murzin, 1998;Russell, Saqi, Sayle, Bates, & Sternberg, 1997;Sangar, Blankenberg, Altman, & Lesk, 2007). In these connections, figuring out residues that are essential for structural integrities and as well residues essential for functional activities of proteins are indispensable to manipulate stabilities and activities of those proteins through protein-engineering strategies from the view of biotechnological and biomedical industries standpoints (Brannigan & Wilkinson, 2002;Leisola & Turunen, 2007;Marcheschi, Gronenberg, & Liao, 2013;Shaw, 1987). Structure, folding and stabilities of cardiotoxin III (CTX III) and short-neurotoxin (SNTX or CBTX, cobrotoxin) belonging to three-finger toxin (TFT) superfamily of snake venom of Naja naja atra (Taiwan cobra) have been well characterized at molecular resolutions and as well at residue-level resolutions (Chang, Lu, Lin, & Yu, 2006;Kumar et al, 1995;Sivaraman, Kumar, & Yu, 1999a;Sivaraman et al, 1999b;Sivaraman, Kumar, Chang, Lin, & Yu, 1998;Sivaraman, Kumar, Jayaraman, Han & Yu, 1997;Sivaraman, Kumar, & Yu, 1996).…”
Section: Introductionmentioning
confidence: 99%